Actualización diagnóstica y terapéutica de la esquizofrenia según su clasificación - Jaramillo Velasteguix, Erika Gisell (2023)
ABSTRACT: Schizophrenia is a chronic and disabling mental illness of unknown etiology that affects approximately 24 million people worldwide with no difference in male and female predominance, schizophrenia is characterized by positive and negative symptoms, which can become partially controlled with the use of antipsychotic drugs, this mental disorder is largely associated with metabolic diseases, which negatively affect the course of the disease, taking into account international data and statistics and without neglecting reports National reports on schizophrenia, this disease requires a specific evaluation and should be considered to put into practice the psychosocial rehabilitation of the patient, the different cognitive disorders of schizophrenia were reviewed and reference was made to the different types and classifications of schizophrenia, Going from its clinical presentation, diagnosis, treatment and complications, in the present work a descriptive investigation with a non-experimental documentary design was applied, the technique used was based on observation for the collection of data and information, the study population was of 60 publications, for this a bibliographic review and compilation was carried out in different scientific articles of studies and clinical cases, in official pages in Google Scholar, Scielo, Pub Med, Science Direct, Medigraphic, which allows to orient the main objective of this work. which is to contribute to the clinical and social management of schizophrenic patients in order to better achieve their quality of life. Keywords: schizophrenia, metabolic syndrome, psychoeducation, treatment.